مروجہ طریقِ اجرت میں حلال و حرام سے متعلق فقہی آرا کا مطالعہ: A Study of Jurisprudential discourses regarding Ḥalāl and Ḥarām in the Prevailing Means of Wages - Sameea Mujahid; Nighat Rasool; Dr. Sami Ullah (Al-Qamar, 2019)
There are many misconceptions among the people about the means that are prevalent in the contemporary world regarding wages in various jobs, whether these are permissible according to Sharīʻah or not? In this age, when interest is often involved in almost all forms of employment, the question has become more important that when the same system is in place, what is the approach to interest and avoid Ḥarām as much as possible. In this article, we look at the Sharīʻah perspective on the various forms of wages in Pakistan. It has been kept in mind that interest seems to be present everywhere in one form or another, but in different cases it is possible to avoid Ḥarām in terms of salary or wages. In this regard, the Sharīʻah position on the three forms of usury system has been discussed: direct interest system, indirect interest system, combination of Ḥalāl and Ḥarām. The study suggests that it is necessary to avoid all the means of livelihood which make it close to suspicion or Ḥarām. Although there is a principle of ease in religion, it is not permissible to go to extremes in order to achieve ease.